2020
DOI: 10.19088/slh.2020.001
|View full text |Cite
|
Sign up to set email alerts
|

Handwashing Compendium for Low Resource Settings: A Living Document, Edition 3

Abstract: Frequent and proper handwashing with soap is vital to prevent the spread of COVID-19. In response, the Sanitation Learning Hub at the Institute of Development Studies has developed this Handwashing Compendium for Low Resource Settings. Bringing existing information from different organisations into one place, the compendium provides guidance, local examples of and further resources on accessible low-cost handwashing facilities, environmental cues and physically distanced hygiene promotion. The compendium is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A systematic review by Saunders-Hastings et al (2017) shows frequent handwashing to have a large and significant protective effect against pandemic influenza. The construction of handwashing stations (e.g., 'tippytaps', which do not require running water) encourages handwashing with soap (Contzen et al, 2015;Coultas et al, 2020). An integrative review on determinants of hand hygiene found consistent evidence that handwashing infrastructure in the household was a determinant of handwashing (White et al, 2020).…”
Section: Studies On Handwashingmentioning
confidence: 99%
“…A systematic review by Saunders-Hastings et al (2017) shows frequent handwashing to have a large and significant protective effect against pandemic influenza. The construction of handwashing stations (e.g., 'tippytaps', which do not require running water) encourages handwashing with soap (Contzen et al, 2015;Coultas et al, 2020). An integrative review on determinants of hand hygiene found consistent evidence that handwashing infrastructure in the household was a determinant of handwashing (White et al, 2020).…”
Section: Studies On Handwashingmentioning
confidence: 99%